Ascending Aortic Aneurysm in Angiotensin II–Infused Mice: Formation, Progression, and the Role of Focal Dissections. Issue 4 (April 2016) - Trachet, Bram; Piersigilli, Alessandra; Fraga-Silva, Rodrigo A.; Aslanidou, Lydia; Sordet-Dessimoz, Jessica; Astolfo, Alberto; Stampanoni, Marco F.M.; Segers, Patrick; Stergiopulos, Nikolaos
Abstract : Objective—: To understand the anatomy and physiology of ascending aortic aneurysms in angiotensin II–infused ApoE −/− mice. Approach and Results—: We combined an extensive in vivo imaging protocol (high-frequency ultrasound and contrast-enhanced microcomputed tomography at baseline and after 3, 10, 18, and 28 days of angiotensin II infusion) with synchrotron-based ultrahigh resolution ex vivo imaging (phase contrast X-ray tomographic microscopy) in n=47 angiotensin II–infused mice and 6 controls. Aortic regurgitation increased significantly over time, as did the luminal volume of the ascending aorta. In the samples that were scanned ex vivo, we observed one or several focal dissections, with the largest located in the outer convex aspect of the ascending aorta. The volume of the dissections moderately correlated to the volume of the aneurysm as measured in vivo ( r 2 =0.46). After 3 days of angiotensin II infusion, we found an interlaminar hematoma in 7/12 animals, which could be linked to an intimal tear. There was also a significant increase in single laminar ruptures, which may have facilitated a progressive enlargement of the focal dissections over time. At later time points, the hematoma was resorbed and the medial and adventitial thickness increased. Fatal transmural dissection occurred in 8/47 mice at an early stage of the disease, before adventita remodeling. Conclusions—: We visualized and quantified the dissections that lead to ascending aortic aneurysms in angiotensin II–infused mice and provided unique insight into the temporal evolution of these lesions. Abstract : Supplemental Digital Content is available in the text.